2007
DOI: 10.1007/s00405-007-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of endoscopic sinus surgery in patients with chronic sinusitis and nasal polyps

Abstract: This study was carried out to compare the outcomes of endoscopic sinus surgery in patients with chronic sinusitis without nasal polyps (CRS) and those with nasal polyps (NP). We also sought to determine the correlation between preoperative computed tomography (CT) findings and postoperative endoscopy and symptom score improvement. Data were collected from two groups of patients diagnosed as CRS with and without nasal polyps that underwent functional endoscopic sinus surgery with a 1-year postoperative follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 16 publications
5
47
0
1
Order By: Relevance
“…We have also demonstrated that the endoscopy score has correlated with the CT score, con rming the observation of Ryan et al or Toros et al (49,50) . In addition, we have observed that the endoscopy score correlates with nasal obstruction (Table 4).…”
Section: Holbrook Et Al Found a Poor Correlation Between Ct Ndingssupporting
confidence: 71%
“…We have also demonstrated that the endoscopy score has correlated with the CT score, con rming the observation of Ryan et al or Toros et al (49,50) . In addition, we have observed that the endoscopy score correlates with nasal obstruction (Table 4).…”
Section: Holbrook Et Al Found a Poor Correlation Between Ct Ndingssupporting
confidence: 71%
“…Deal et al has demonstrated worse results of QOL in patients of NP and hypothesized it due to mass effect of polyps causing blockage, reduced mucociliary clearance, retained secretions, increased mucosal oedema and inflammation and reduced sense of smell [19]. Toros et al in their study of symptoms have observed higher symptom scores and worse objective findings in patients of NP [20]. Contrary to the above studies Smith et al in a study of preoperative factors that predict surgical outcome and Poetker et al on the outcomes of ESS on chronic rhinosinusitis with NP have found better preoperative CSS scores in patients with NP resulting in a positive impact on the QOL [21,22].…”
Section: Discussionmentioning
confidence: 94%
“…Various authors have observed significantly higher scores in patients of NP as compared to CRS [20]. The endoscopic scoring of Lund Kennedy is based on presence of oedema and polyps and CT scan scores of Lund Mackay on presence of mucosal oedema and opacification of sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Toros et al in one study proved that endoscopic sinus surgery provides significant symptomatic relief and endoscopically evident healing in patients with CRS and nasal polyps. 22 They recorded the preoperative symptom and endoscopic scores, and postoperative symptom and endoscopic scores using VAS. Our study has focussed on the correlations between all the three parameters.…”
Section: Preoperative Correlationsmentioning
confidence: 99%